Glass-resin laminate and method for producing glass-resin laminate

By performing the drying process before the bonding process of the glass resin laminate, the amount of moisture in the thermoplastic adhesive is reduced, and the problem of large haze change rate in the important temperature region in the prior art is solved, haze control when the temperature is low is realized, and product reliability is improved.

CN119550701APending Publication Date: 2025-03-04NIPPON ELECTRIC GLASS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411068699.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-01
Filing Date
2024-08-05
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The conventional glass resin laminate has a large change rate of haze value relative to temperature change in important temperature areas, resulting in excessive haze when the temperature is low, making it blurry so that it is difficult to visually confirm the back side.

Method used

A thermoplastic adhesive layer is sandwiched between the glass plate and the resin plate, and a drying process is performed before the bonding process to reduce the amount of moisture in the thermoplastic adhesive, thereby reducing the rate of change of haze value in the temperature range of 10°C to 30°C.

Benefits of technology

By reducing the change rate of haze value with respect to temperature change, the glass resin laminate is suppressed from being blurred in an important temperature region to the point where it is difficult to visually confirm the back side, and the reliability of the product is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119550701A_ABST
    Figure CN119550701A_ABST
Patent Text Reader

Abstract

Provided are a glass-resin laminate and a method for producing a glass-resin laminate, whereby the rate of change in haze value with respect to temperature change can be sufficiently reduced in an important temperature range when the glass-resin laminate is used. A glass-resin laminate (1) in which a thermoplastic adhesive layer (3) is interposed between a glass plate (4) and a resin plate (2), and in which Hb / Ha is 1.0-1.25, where Ha% is the haze value measured in accordance with the standard of JIS K7136 (2000) in an atmosphere at a temperature of 30 DEG C and a relative humidity of 40%, and Hb% is the haze value measured in accordance with the standard in an atmosphere at a temperature of 10 DEG C and a relative humidity of 40%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a glass-resin laminate having a thermoplastic adhesive layer interposed between a glass plate and a resin plate, and a method for producing the same. Background Art

[0002] In a wide range of fields such as cover members of various devices and building materials, glass resin laminates formed by laminating and integrating glass plates on both sides of a resin plate via an adhesive layer are often used from the viewpoint of achieving a balance between durability and lightness.

[0003] In recent years, in order to achieve further weight reduction, glass plates using very thin glass sheets have been proposed or put into practical use as glass plates of glass resin laminates (for example, refer to Patent Documents 1 to 3).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2012-25152

[0007] Patent Document 2: Japanese Patent Application Publication No. 2014-12373

[0008] Patent Document 3: Japanese Patent Application Publication No. 2014-65169 Summary of the invention

[0009] Problems to be solved by the invention

[0010] The present inventors have noticed that the rate of change of the haze value of the conventional glass resin laminate with respect to the temperature change (the rate of change of haze) is large during long-term research. The present inventors have particularly noticed that the rate of change of the haze value with respect to the temperature change is too large in the important temperature range when the glass resin laminate is used during further research. In addition, the present inventors have found that when the temperature is low in the above-mentioned temperature range, the glass resin laminate becomes hazy (white turbid) due to the excessive haze value, and it is difficult to visually confirm the back side from the front side.

[0011] From the above viewpoints, an object of the present invention is to reduce the rate of change of the haze value with respect to temperature change in an important temperature range when using a glass resin laminate.

[0012] Solutions to Solve Problems

[0013] (1) A first aspect of the present invention made to solve the above-mentioned problems is a glass resin laminate, in which a thermoplastic adhesive layer is sandwiched between a glass plate and a resin plate, and the glass resin laminate is characterized in that, when the haze value measured in accordance with the standard of JIS K7136 (2000) in an atmosphere at a temperature of 30°C and a relative humidity of 40% is set to Ha%, and the haze value measured in accordance with the said standard in an atmosphere at a temperature of 10°C and a relative humidity of 40% is set to Hb%, Hb / Ha is 1.0 to 1.25.

[0014] According to the glass resin laminate, the rate of change of the haze value with respect to the temperature change is sufficiently reduced in the temperature range of 10°C to 30°C. In other words, in the process of changing the temperature from 30°C to 10°C, the haze value is less likely to change than in the past. In this case, the temperature range of 10°C to 30°C corresponds to the temperature range of the house or indoors where the glass resin laminate is mainly used, so it can be said to be an important temperature range. Here, according to the experimental results obtained by the present inventors, the above-mentioned Hb / Ha in the conventional glass resin laminate exceeds 1.3. Therefore, in the past, when the temperature was low in the above-mentioned temperature range, the haze value was too large, and the glass resin laminate was blurred to the extent that it was difficult to visually confirm the back side from the surface side. In contrast, according to the glass resin laminate having the structure here, the above-mentioned Hb / Ha is 1.0 to 1.25, so even when the temperature is low in the above-mentioned temperature range, the blurring is suppressed to the extent that it is difficult to visually confirm the back side from its surface side.

[0015] (2) In the configuration of (1) above, the haze value measured in accordance with the above standard in an atmosphere having a temperature of 10° C. and a relative humidity of 40% may be 4.5% or less.

[0016] Here, according to the experimental results obtained by the present inventors, the haze value in the conventional glass resin laminate exceeds 4.5%. Therefore, the probability that the glass resin laminate is hazy to the extent that it is difficult to visually confirm the back side from the front side at a temperature of around 10°C is extremely high. In contrast, according to the glass resin laminate having the structure herein, the haze value is 4.5% or less in an atmosphere at a temperature of 10°C and a relative humidity of 40%, so the probability that the glass resin laminate is hazy to the extent that it is difficult to visually confirm the back side from the front side at a temperature of around 10°C is greatly reduced.

[0017] (3) In the structure described in (1) or (2) above, the thermoplastic adhesive layer may be an adhesive layer composed of EVA (ethylene vinyl acetate-based thermoplastic resin).

[0018] In this way, the characteristics of EVA (such as excellent transparency and fixability) can be effectively utilized to efficiently ensure the advantages described above.

[0019] Here, the inventors have repeatedly conducted in-depth studies and have come to the conclusion that the reason why the rate of change of the haze value of conventional glass resin laminates in the temperature range of 10°C to 30°C with respect to temperature change is too large is because the thermoplastic adhesive layer contains a large amount of water. Based on this conclusion, the following inventions (4) to (7) have been made. Furthermore, this conclusion has become the basis for deriving the above (1) to (7).

[0020] (3) The structure is an important factor of the invention.

[0021] (4) The second aspect of the present invention, which is made to solve the above-mentioned problems, is a method for manufacturing a glass resin laminate, comprising: a lamination step of forming a temporary laminate in which a sheet of thermoplastic adhesive is sandwiched between a glass plate and a resin plate; and a bonding step of heating the temporary laminate to bond the glass plate to the resin plate, wherein the method for manufacturing a glass resin laminate is characterized in that, before the bonding step, a drying step of drying the sheet of thermoplastic adhesive is performed.

[0022] According to this structure, the moisture content of the sheet-shaped thermoplastic adhesive is reduced by performing the drying process, so the rate of change of the haze value relative to the temperature change in the temperature range of 10°C to 30°C can be reduced. In this case, it is preferred to perform the bonding process within a short time (for example, within 2 hours) after the drying process to avoid the reduced moisture content in the thermoplastic adhesive from increasing again. In addition, the thermoplastic adhesive layer of the glass resin laminate obtained by performing the drying process and the bonding process is maintained in a state of reduced moisture content for a long time due to the presence of the glass plate and the resin plate in the humidity range (for example, humidity 20% to 80%) in the room or indoor where the glass resin laminate is mainly used. Therefore, according to the glass resin laminate, it is possible to suppress blurring for a long time to the extent that it is difficult to visually confirm the back side from its surface side.

[0023] (5) In the configuration of (4) above, a drying step may be performed before the lamination step.

[0024] In this manner, insufficient drying or poor drying of the sheet-shaped thermoplastic adhesive due to the drying step being performed after the lamination step can be suppressed.

[0025] (6) In the configuration of (4) or (5) above, the drying step may be performed by drying under reduced pressure.

[0026] In this way, it is not necessary to excessively heat the thermoplastic adhesive during the drying step, and thus it is possible to suppress the thermoplastic resin adhesive from being excessively softened and melted by heat before the bonding step.

[0027] (7) In any one of the above structures (4) to (6), in the drying step, reduced pressure drying may be performed at a temperature of 45° C. or less and a pressure of 0.1 MPa or less.

[0028] In this way, by performing the drying process at a temperature below 45°C, the sheet-shaped thermoplastic adhesive will not become too soft and melt due to heat. As a result, the subsequent lamination process and bonding process can be smoothly carried out without obstacles. In addition, by performing the drying process at a pressure below 0.1 MPa, efficient drying can be achieved. Therefore, according to the structure here, it is possible to achieve both prevention of melting of the sheet-shaped thermoplastic adhesive and reliable shortening of the production interval time.

[0029] Effects of the Invention

[0030] According to the present invention, the rate of change of the haze value with respect to the temperature change can be sufficiently reduced in a temperature range that is important when using a glass resin laminate. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a longitudinal sectional front view showing the glass resin laminate according to the embodiment of the present invention.

[0032] Figure 2 This is a flowchart showing a method for producing a glass resin laminate according to an embodiment of the present invention.

[0033] Figure 3 It is a perspective view for explaining a preparation step in the method for producing a glass resin laminate according to the embodiment of the present invention.

[0034] Figure 4 It is a perspective view for explaining the drying step in the method for producing the glass resin laminate according to the embodiment of the present invention.

[0035] Figure 5 It is a perspective view for explaining a lamination step in the method for producing a glass resin laminate according to the embodiment of the present invention.

[0036] Figure 6 It is a diagram for explaining an embodiment of the present invention.

[0037] Description of Reference Numerals

[0038] 1Glass resin laminate

[0039] 1a Temporary laminate

[0040] 2 resin board

[0041] 3. Adhesive layer (thermoplastic adhesive layer)

[0042] 3a Adhesive (thermoplastic adhesive)

[0043] 4 Glass Plates

[0044] 5. Surface of glass-resin laminate

[0045] 6 Back side of glass resin laminate

[0046] S2 Drying process

[0047] S3 Lamination Process

[0048] S4 bonding process. DETAILED DESCRIPTION

[0049] Hereinafter, a glass resin laminate and a method for producing the same according to an embodiment of the present invention will be described with reference to the drawings.

[0050] like Figure 1 As shown, the glass resin laminate 1 of this embodiment is formed by laminating and integrating transparent glass plates 4 on both sides of a transparent resin plate 2 via transparent adhesive layers 3. The glass resin laminate 1 is configured in a rectangular shape, but is not limited to this shape.

[0051] The thickness of the resin plate 2 is 0.01 to 20 mm, more preferably 0.05 to 15 mm, and even more preferably 0.1 to 10 mm.

[0052] As the material of the resin plate 2, polycarbonate is preferably used, but polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), polyetheretherketone (PEEK), polyamide (PA), polyvinyl chloride (PVC), polyethylene (PE), polypropylene (PP), polyethylene naphthalate (PEN), etc. can also be used.

[0053] The adhesive layer 3 is a thermoplastic adhesive layer. As the material of the thermoplastic adhesive layer 3, EVA (ethylene-vinyl acetate thermoplastic resin) is used. The thickness of the adhesive layer 3 is 10 to 2000 μm, more preferably 50 to 1000 μm from the viewpoint of adhesive strength, and preferably 10 to 1000 μm from the viewpoint of durability.

[0054] The glass plate 4 is preferably a glass plate thinner than the resin plate 2, and its thickness is 2000 μm or less, preferably 10 to 1000 μm in terms of weight, and more preferably 30 to 800 μm. It should be noted that the thickness of the glass plate 4 is preferably thinner than the thickness of the adhesive layer 3. It should be noted that the thickness of the glass plate 4 may be outside the above range.

[0055] As the material of the glass plate 4, silicate glass or silica glass is used, and preferably borosilicate glass, soda-lime glass, aluminosilicate glass, alkali-free glass, etc. are used. Here, the so-called alkali-free glass refers to glass that does not substantially contain alkali components (alkali metal oxides), specifically, glass in which the weight ratio of alkali components is 3000 ppm or less. The weight ratio of alkali components in the present invention is preferably 1000 ppm or less, more preferably 500 ppm or less, and further preferably 300 ppm or less.

[0056] The glass sheet 4 can be formed by the known float method, flattening method, slot down-draw method, redraw method, etc., but is preferably formed by the overflow down-draw method. The overflow down-draw method is a method in which molten glass flows into an overflow trough provided at the upper part of a forming body having a substantially wedge-shaped cross section, and the molten glass overflowing from the overflow trough to both sides flows down along the side walls of both sides of the forming body while being fused and integrated at the lower end of the forming body, thereby continuously forming glass sheets 4 one by one.

[0057] The glass resin laminate 1 composed of the above components has a haze value measured in accordance with the standard of JIS K7136 (2000) at a temperature of 30°C and a relative humidity of 40% as Ha%, and a haze value measured in accordance with the standard at a temperature of 10°C and a relative humidity of 40% as Hb%, and Hb / Ha is 1.0 to 1.25.

[0058] According to the glass resin laminate 1, the rate of change of the haze value with respect to the temperature change is sufficiently small in the temperature range of 10°C to 30°C. In other words, according to the glass resin laminate 1, the haze value is less likely to change in the process of changing the temperature from 30°C to 10°C than in the past. In this case, the temperature range of 10°C to 30°C corresponds to the temperature range of the room or indoors where the glass resin laminate 1 is mainly used, and can be said to be an important temperature range. Here, according to the experimental results obtained by the present inventors, the above-mentioned Hb / Ha in the conventional glass resin laminate exceeds 1.3 (details will be described later). Therefore, in the past, when the temperature was low in the above-mentioned temperature range, the glass resin laminate was blurred (white turbid) to the extent that it was difficult to visually confirm the back side from the surface side due to the excessive haze value. In contrast, according to the glass resin laminate 1, since the above-mentioned Hb / Ha is 1.0 to 1.25, even when the temperature is low in the above-mentioned temperature range, it is possible to suppress blurring to the extent that it is difficult to visually confirm the back side 6 from its surface 5 side. It should be noted that the above Hb / Ha is more preferably 1.0 to 1.15, and even more preferably 1.0 to 1.10.

[0059] The glass resin laminate 1 has a haze value of 4.5% or less measured in accordance with JIS K7136 (2000) in an atmosphere at a temperature of 10° C. and a relative humidity of 40%.

[0060] Here, according to the experimental results obtained by the present inventors, the haze value of the conventional glass resin laminate exceeds 4.5% (details will be described later), so the probability that the glass resin laminate is hazy to the extent that it is difficult to visually confirm the back side from the front side at a temperature of around 10°C is extremely high. In contrast, according to the glass resin laminate 1, since the haze value measured in accordance with the standard of JIS K7136 (2000) in an atmosphere at a temperature of 10°C and a relative humidity of 40% is 4.5% or less, the probability that the glass resin laminate 1 is hazy to the extent that it is difficult to visually confirm the back side 6 from the front side 5 at a temperature of around 10°C is greatly reduced. It should be noted that the haze value is more preferably 4.0% or less, and further preferably 3.7% or less.

[0061] Next, a method for manufacturing the glass resin laminate 1 having the above-mentioned structure will be described. Figure 2 As shown, the manufacturing method includes a preparation step S1, a drying step S2, a lamination step S3, and a bonding step S4.

[0062] In the preparation step S1, Figure 3 As shown, one resin plate 2, two glass plates 4, and two sheet-shaped adhesives 3a are prepared.

[0063] In the drying step S2, Figure 4 As shown, two sheets of adhesive 3a prepared in the preparation step S1 are taken out and dried by reduced pressure drying. These adhesives 3a are all thermoplastic adhesives and are composed of EVA (ethylene-vinyl acetate thermoplastic resin). By performing the drying step S2, the laminating step S3 and the bonding step S4, the adhesive layers 3 of the glass resin laminate 1 described above are formed.

[0064] In the drying step S2, specifically, the two sheets of adhesive 3a are dried under reduced pressure at a temperature of 45°C or lower and a pressure of 0.1 MPa or lower.

[0065] In this case, when the drying process is performed at a temperature exceeding 45°C, the sheet-like adhesive 3a may become too soft and melt due to the heat, which may cause obstacles to the subsequent lamination process S3 and bonding process S4 or reduce the quality of the glass resin laminate 1. Specifically, the sheet-like adhesive 3a melts, and the thickness of the sheet becomes uneven. As a result, the adhesion of the adhesive 3a becomes uneven, and the glass plate 4 may be easily peeled off. In addition, when the drying process is performed at a pressure exceeding 0.1MPa, efficient drying may not be possible. On the other hand, in the above-mentioned reduced pressure drying, these undesirable situations will not occur. Therefore, according to the above-mentioned reduced pressure drying, it is possible to achieve both prevention of melting of the sheet-like adhesive 3a and sufficient shortening of the production interval time.

[0066] In addition, the weight reduction rate of the sheet-shaped adhesive 3a caused by the drying step S2 is preferably 0.1% or more. Here, the weight reduction rate is calculated by (W1-W2) / W1(%), when the weight of the sheet-shaped adhesive 3a before the drying step S2 is W1 and the weight of the sheet-shaped adhesive 3a after the drying step S2 is W2. This weight reduction rate is considered to be caused by the reduction of water content in the sheet-shaped adhesive 3a.

[0067] As described above, the moisture content of the sheet-shaped adhesive 3a is reduced by performing the drying step S2, thereby reducing the rate of change of the haze value in the temperature range of 10°C to 30°C with respect to the temperature change. Furthermore, the adhesive layer 3 of the glass resin laminate 1 obtained by performing the laminating step S3 and the bonding step S4 after the drying step S2 is maintained in a state of reduced moisture content for a long time due to the presence of the glass plate 4 and the resin plate 2 in the humidity range (for example, humidity 20% to 80%) inside the house or indoor where the glass resin laminate 1 is mainly used. Therefore, according to the obtained glass resin laminate 1, it is possible to suppress haze for a long time to the extent that the back side 6 is difficult to visually confirm from the front side 5 thereof.

[0068] In the lamination step S3, Figure 5 As shown, the resin plate 2 prepared in the preparation step S1, the two sheets of adhesive 3a after the drying step S2, and the two glass plates 4 prepared in the preparation step S1 are overlapped to form a temporary laminate 1a. The drying step S2 is performed before the lamination step S3, thereby preventing the sheet of adhesive 3a from being insufficiently dried or poorly dried.

[0069] In the bonding process S4, the temporary laminate 1a formed by the lamination process S3 is heated. In detail, in the bonding process S4, the temporary laminate 1a is bonded by heat compression, for example, using an autoclave device. As a result, the sheet-like adhesive 3a softens to form an adhesive layer 3, thereby integrating the resin plate 2 and the glass plate 4. In this case, the time from the end of the drying process S2 to the execution of the bonding process S4 is preferably short (for example, within 2 hours). In this way, the moisture content of the adhesive 3a that has been reduced by the execution of the drying process S2 is suppressed from increasing again. In addition, at the moment when the bonding process S4 is completed, Figure 1 The glass-resin laminate 1 is shown.

[0070] [Example]

[0071] The present inventors carried out the above-described preparation step S1, drying step S2, lamination step S3, and bonding step S4 to manufacture four types of glass resin laminates 1. The weight reduction rate (water reduction rate) of the sheet-shaped adhesive 3a obtained by carrying out the drying step S2 of the four types of glass resin laminates 1 was different. The water reduction rate of the first glass resin laminate 1 (Example 1) was 0.10%, the water reduction rate of the second glass resin laminate 1 (Example 2) was 0.12%, and the water reduction rate of the third glass resin laminate 1 (Example 3) was 0.13%. In this case, in all Examples 1 to 3, reduced pressure drying was carried out at a temperature of 45° C. or less (here 30° C.) and a pressure of 0.1 MPa or less (here 80 Pa) for 120 minutes in the drying step S2. And, after the reduced pressure drying, the bonding step S4 was carried out 30 minutes later. In addition, the fourth glass resin laminate 1 (comparative example) did not perform the drying step S2 on the sheet-shaped adhesive 3a, so the above-mentioned water reduction rate was 0.00. In addition, the haze values ​​of the four types of glass resin laminates 1 were measured at temperatures of 10° C., 20° C., 30° C., and 40° C. The relative humidity during the measurement was 40%. In addition, the haze values ​​were all haze values ​​measured in accordance with the standard of JIS K7136 (2000).

[0072] The above measurement results were Figure 6 The graph of and the following Table 1 show. Figure 6In the figure, Example 1 (moisture reduction rate: 0.10) is shown by a single-dot chain curve L1, and the measurement points at 10°C to 40°C are shown as A to D, respectively. In addition, in the figure, Example 2 (moisture reduction rate: 0.12) is shown by a dotted line curve L2, and the measurement points at 10°C to 40°C are shown as E to H, respectively. Moreover, in the figure, Example 3 (moisture reduction rate: 0.13) is shown by a solid line curve L3, and the measurement points at 10°C to 40°C are shown as I to L, respectively. In contrast to these, in the figure, a comparative example (moisture reduction rate: 0.00) is shown by a double-dot chain curve Lx, and the measurement points at 10°C to 40°C are shown as M to P, respectively.

[0073] In the following Table 1, the haze values ​​(%) of each of the A to D points in Example 1, the haze values ​​(%) of each of the E to H points in Example 2, the haze values ​​(%) of each of the I to L points in Example 3, and the haze values ​​(%) of each of the M to P points in the comparative example are described as numerical values. It should be noted that these haze values ​​are average values ​​calculated based on the haze values ​​(%) of 10 glass resin laminates 1 of each of the four types, which were manufactured.

[0074]

Table 1

[0075]

[0076] according to Figure 6 As can be seen from the graph and the above-mentioned Table 1, the haze values ​​of Examples 1 to 3 and Comparative Examples are within the range of 2.42 to 2.49 at 40°C, and the haze values ​​of each are small and very close values. In contrast, the haze values ​​of Examples 1 to 3 increase as the temperature shifts from 30°C to 10°C, but the degree of increase is small. In other words, the rate of change of the haze value is small. On the other hand, the haze value of the Comparative Example increases greatly as the temperature shifts from 30°C to 10°C. In other words, the rate of change of the haze value is extremely large.

[0077] Here, according to the above Table 1, the maximum haze value at a temperature of 10°C in Examples 1 to 3 is 4.23% in Example 1, which is much lower than 4.5%. In contrast, the haze value at a temperature of 10°C in the comparative example is 4.83%, which is much higher than 4.5%. Thus, when the haze value at a temperature of 10°C is 4.5% or less, the glass resin laminate 1 can be suppressed from being blurred to the extent that the back surface 6 side is difficult to visually confirm from the front surface 5 side. In addition, the haze value at a temperature of 10°C in Example 2 is 3.82%, and the haze value at a temperature of 10°C in Example 3 is 3.61%, which can effectively suppress blurring.

[0078] In addition, considering the above-mentioned Table 1, the haze value C at a temperature of 30°C in Example 1 is 3.43% and the haze value A at a temperature of 10°C is 4.23%, so A / C is 1.23. The haze value G at a temperature of 30°C in Example 2 is 3.53% and the haze value E at a temperature of 10°C is 3.82%, so E / G is 1.08. The haze value K at a temperature of 30°C in Example 3 is 3.33% and the haze value I at a temperature of 10°C is 3.61%, so I / K is 1.08. In contrast, the haze value O at a temperature of 30°C in the comparative example is 3.67% and the haze value M at a temperature of 10°C is 4.83%, so M / O is 1.32.

[0079] As mentioned above, although embodiment of this invention is described, embodiment of this invention is not limited to this, Various changes can be made without departing from the scope of the gist of this invention.

[0080] For example, in the above embodiment, the glass resin laminate 1 is integrated by laminating the glass plates 4 on both sides of the resin plate 2 via the adhesive layer 3 , but the glass plate 4 may be laminated and integrated only on one side of the resin plate 2 via the adhesive layer 3 .

[0081] In the above embodiment, a single adhesive layer 3 is interposed between the glass plate 4 and the resin plate 2, but two or more adhesive layers 3 may be interposed. In this case, it is preferred that both of the two or more adhesive layers 3 are dried under reduced pressure in the drying step S2.

[0082] In the above-described embodiment, an adhesive made of EVA is used as the thermoplastic adhesive 3 a , but an adhesive made of PVA (polyvinyl alcohol) or the like may be used, for example.

[0083] In the above-described embodiment, the adhesive 3 a is dried under reduced pressure in the drying step, but the drying may be performed without reducing pressure.

[0084] In the above-described embodiment, the drying step S2 is performed before the laminating step S3 , but the drying step S2 may be performed after the laminating step S3 and before the bonding step S4 .

[0085] In the above embodiment, the resin plate 2, the adhesive layer 3 and the glass plate 4 are transparent. However, the “transparency” does not require that the above 2, 3, 4 are colorless and transparent, and at least one of the above 2, 3, 4 may be colored.

Claims

1. A glass-resin laminate, wherein a thermoplastic adhesive layer is sandwiched between a glass plate and a resin plate, The glass resin laminate is characterized in that: When the haze value measured in accordance with the standard of JIS K7136 (2000) at a temperature of 30°C and a relative humidity of 40% is referred to as Ha%, and the haze value measured in accordance with the standard at a temperature of 10°C and a relative humidity of 40% is referred to as Hb%, Hb / Ha is 1.0~1.

25.

2. The glass resin laminate according to claim 1, wherein: The haze value measured in accordance with the above-mentioned standard in an atmosphere of a temperature of 10° C. and a relative humidity of 40% is 4.5% or less.

3. The glass resin laminate according to claim 1 or 2, characterized in that: The thermoplastic adhesive layer is an adhesive layer composed of EVA (ethylene-vinyl acetate-based thermoplastic resin).

4. A method for manufacturing a glass resin laminate, comprising: A lamination step of forming a temporary laminated body in which a sheet of thermoplastic adhesive is sandwiched between the glass plate and the resin plate; and a bonding step of heating the temporary laminate to bond the glass plate to the resin plate, The method for producing a glass resin laminate is characterized in that: Before the bonding step, a drying step of drying the sheet-shaped thermoplastic adhesive is performed.

5. The method for producing a glass resin laminate according to claim 4, wherein: The drying process is performed before the laminating process.

6. The method for producing a glass resin laminate according to claim 4 or 5, wherein: In the drying step, drying is performed under reduced pressure.

7. The method for producing a glass resin laminate according to claim 6, wherein: In the drying step, reduced-pressure drying is performed at a temperature of 45° C. or lower and a pressure of 0.1 MPa or lower.

Citation Information

Patent Citations

  • Glass film laminate

    JP2012025152A

  • Glass resin laminate

    JP2014012373A

  • Glass film laminate for display object cover

    JP2014065169A